Adjunct Extraposition: Base Generation or Movement?. (19th June 2017) - Reeve, Matthew; Hicks, Glyn
Abstract: It has been argued that extraposition from DP is derived differently according to whether a complement or an adjunct is extraposed, with complement extraposition being derived by movement and adjunct extraposition being derived via covert Quantifier Raising (QR) of the host DP plus Late Merge of the adjunct (Fox & Nissenbaum 1999). We argue that adjunct extraposition is itself derivationally ambiguous and may be derived either by movement of the adjunct or by base generation of the adjunct in extraposed position. Accordingly, we argue for a relaxation of the strictly compositional view that nominal modification is always mediated by syntactic sisterhood. We argue that whereas base‐generated extraposition is possible with quantificational host DPs, adjunct extraposition from definites must be derived by movement. This accounts for a number of asymmetries between extraposition from definites and from other types of DP, concerning reconstruction for condition C, scope reconstruction, and information‐structural restrictions on extraposition.